1983
DOI: 10.1210/jcem-57-4-863
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary and Adrenal Responses to the Anti-Progesterone and Anti-Glucocorticoid Steroid Ru 486 in Primates1

Abstract: RU 486 is a synthetic steroid with anti-progesterone and anti-glucocorticoid properties. While studying its acute effects on pituitary hormone secretion in cynomolgus monkeys, we found that RU 486 inhibited PRL secretion induced by an estrogen-progesterone synergy (P less than 0.025). By contrast, plasma levels of ACTH, arginine vasopressin and cortisol increased following RU 486 administration (P less than 0.05). Plasma FSH, LH, GH and TSH were unaffected by RU 486 treatment. Our findings suggest potential di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…It is well known that RU 38486 also binds to glucocorticoid receptors and has potent antiglucocorticoid activity for a number of biological responses (35)(36)(37). In agreement with such observations, we found that several natural adrenal corticoids and the synthetic glucocorticoid triamcinolone were able to displace [ 3 H]RU 38486 from binding sites in HPOA cytosols.…”
Section: Discussionsupporting
confidence: 89%
“…It is well known that RU 38486 also binds to glucocorticoid receptors and has potent antiglucocorticoid activity for a number of biological responses (35)(36)(37). In agreement with such observations, we found that several natural adrenal corticoids and the synthetic glucocorticoid triamcinolone were able to displace [ 3 H]RU 38486 from binding sites in HPOA cytosols.…”
Section: Discussionsupporting
confidence: 89%
“…In animals and humans with an intact hypothalamic-pituitary-adrenal (HPA) axis, RU 486 antagonizes the negative feedback of cortisol by blocking central GRs (2,18). The increase in plasma ACTH and cortisol levels induced by RU 486 is particularly evident in the early morning hours, when ACTH and cortisol concentrations are physiologically peaking (19).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…MIF, also designated RU486 (Roussel Uclaf, Population Council), was the first antiprogestational agent synthesized and tested (14,15) and is considered to be the prototype antiprogestin. MIF is a steroid [17ß-hydroxy-11ß-(4-dimethylaminophenyl)-17α-(prop-1-ynyl)estra-4,9-dien-3-one] that has high affinity for PR, mediating its significant antiprogestational effects (15)(16)(17)(18)(19). When MIF binds to PR, progesterone is blocked from binding the PR and progesteronemediated transcription is inhibited (20,21).…”
Section: Introductionmentioning
confidence: 99%